The Study on Estimation and Quality Control of Residential G+3 Building - Gireesh Babu, Sunil Biradar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
An estimate is a computation of the quantities required and expenditure likely to be incurred the construction of a work. In any construction project, the probable cost of construction which is known beforehand is known as the estimated cost. And hence it is quite essential for the arrangement of financial resources for the completion of any construction project. In this project, the main aim was to find out the detailed estimate of quantities of all the structural aspect of G+3 building. The Sunway Opus Grand Neville is a result of a joint venture between Sunway City of Malaysia and Opus of Hyderabad, India. It also aims in finding out the probable cost, or the estimated cost of the project based on the computation of these quantities. The structural aspects considered for the estimation of quantities are earthwork in excavation and backfilling, concrete work in foundation and in R.C.C structures such as beams, columns, slabs, staircases etc., steel reinforcement in beams, columns and other R.C.C structures and brickwork in superstructure. The computation of quantities was carried out based on the drawings of various structural elements, such as the each floor plan, footings and columns layout, beams layout, staircases layout, footing specifications and column specifications, which have also been provided in this document. These details provide an idea for requirement of quantities for a project and also the likely expenditure which would be needed to be arranged. This documentation also provides the abstract of the estimated cost for the structural aspects.